Family routines and rituals in the context of chronic conditions: A review. (15th July 2013) - Crespo, Carla; Santos, Susana; Canavarro, Maria Cristina; Kielpikowski, Magdalena; Pryor, Jan; Féres‐Carneiro, Terezinha
<x xml:space="preserve">Abstract</x> This paper is a systematic review of 39 empirical studies on family routines and rituals in the context of a chronic condition of a family member. The search strategy encompassed a wide spectrum of chronic conditions affecting family members from childhood/adolescence to adulthood. Twenty quantitative, 13 qualitative, 3 mixed‐methods, and 3 intervention studies published between 1995 and 2012 were reviewed. A conceptual framework of routines and rituals as key elements of family health was adopted, resulting in three main findings. First, a chronic condition in a family member impacted the frequency and nature of family's routines and rituals. Second, these whole‐family interactions held important functions for individuals and families, constituting strategic resources in the condition's management and opportunities for emotional support exchanges, and providing the family with a sense of normalcy amid the challenges posed by chronic conditions. Third, family routines and rituals were linked to positive health and adaptation outcomes for both patients and family members. Implications for future research include the need for the distinction between routines and rituals against a conceptual background, use of validated assessment methods, and empirical examination of predictors of changes in routines and rituals throughout the course of the condition and of the mechanisms linking these family events to positive outcomes. Conclusions support the inclusion of routines and rituals in a family‐centered care approach to the understanding and treatment of chronic conditions.